Performance of HIV pre-exposure prophylaxis indirect adherence measures among men who have sex with men and transgender women: Results from the PrEP Brasil Study - Marins, Luana M. S. (PLoS One, 2019)
INTRODUCTION: Efficacy of daily emtricitabine/tenofovir disoproxil fumarate (FTC/TDF) for PrEP is strongly dependent on the adherence. We examined the concordance between indirect adherence measures and protective drug levels among participants retained through 48 weeks in the PrEP Brasil Study. METHODS: PrEP Brasil was a prospective, multicenter, open-label demonstration project evaluating PrEP provision for men who have sex with men (MSM) and transgender women (TGW) at higher risk for HIV infection within the setting of Brazilian Public Health System. Three indirect adherence measures were obtained at week 48: medication possession ratio (MPR), pill count and self-report (30-days recall). Tenofovir diphosphate (TFV-DP) concentration in Dried Blood Spot (DBS) was measured at week 48. Areas under (AUC) the receiver operating characteristics (ROC) curve were used to evaluate the concordance between achieving protective drug levels (TFV-DP≥700fmol/punch) and the indirect adherence measures. Youden’s index and distance to corner were used to determine the optimal cutoff points for each indirect adherence measure. We calculated sensitivity, specificity, negative (NPV) and positive (PPV) predictive values for the found cutoff points. Finally, Delong test was used to compare AUCs. RESULTS AND DISCUSSION: From April, 2014 to July, 2016, 450 participants initiated PrEP, 375(83.3%) were retained through 48 weeks. Of these, 74% (277/375) had TFV-DP ≥700fmol/punch. All adherence measures discriminated between participants with and without protective drug levels (AUC>0.5). High indirect adherence measure was predictive of protective drug levels (PPV>0.8) while low indirect adherence measure was not predictive of lack of protective drug levels (NPV<0.5). No significant differences were found between the adherence methods (p = 0.44). CONCLUSIONS: Low-burden measurements such as MPR and self-report can be used to predict PrEP adherence in a public health context in Brazil for MSM and TGW retained through 48 weeks. Clinical Trial Number: NCT01989611.